How do geometric constraints influence migration patterns? - Thorup, K.; Rahbek, C. (Animal Biodiversity and Conservation, 2004)
Null models exclusively invoking geometric constraints have recently been demonstrated to provide new insight as to what explains geographic patterns of species richness and range size distribution. Analyses of migration patterns have traditionally been conducted in the absence of appropriate simulations and analytical models. Here we present a null model exclusively invoking geometric constraints and a more advanced analytical model incorporating spread along a migration direction that allow investigation of the influence of physiographical and physiological boundaries for terrestrial taxa, with ocean and sea as geometric constraints, in relation to observed patterns of migration. Our models take into account the low recovery probability of terrestrial taxa over sea. The null model was not found to explain any of the directional variation in the ring-recoveries, but when comparing the distribution of data modeled using a simple clock-and-compass model with distributions of ring-recoveries, geometric constraints were found to explain up to 22% of the variation in ring-recoveries. However, the assumed directional concentrations per step used in the model were much higher than expected, and the qualitative fit of the model was rather poor even when non¿terrestrial sites of recoveries were excluded.